2004
DOI: 10.1093/molehr/gah099
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell apoptosis markers and pathways in human ejaculated sperm: potential utility as indicators of sperm quality

Abstract: In this study we extended earlier work to determine whether sperm respond to somatic cell apoptotic stimuli and whether apoptotic phenotypes are significant indicators of human sperm quality. We evaluated ejaculated sperm from fertile donors and subfertile patients following purification of fractions of high and low motility. In unstimulated conditions, caspase enzymatic activity was higher in motile fractions from subfertile patients than in donors, and was higher in low motility fractions from both groups. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 72 publications
6
78
0
6
Order By: Relevance
“…Apoptosis is an ongoing physiological phenomenon that maintains the number of germ cells within the supportive capacity of the Sertoli cells [19]. Although ejaculated spermatozoa display several apoptosis-like characteristics, these apoptosis-related features do not necessarily indicate death functions [20]. Nevertheless, the apoptosis-like phenotype of ejaculated sperm has been associated with the presence of abnormal spermatozoa in semen [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is an ongoing physiological phenomenon that maintains the number of germ cells within the supportive capacity of the Sertoli cells [19]. Although ejaculated spermatozoa display several apoptosis-like characteristics, these apoptosis-related features do not necessarily indicate death functions [20]. Nevertheless, the apoptosis-like phenotype of ejaculated sperm has been associated with the presence of abnormal spermatozoa in semen [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to eliminate these abnormal spermatozoa during spermatogenesis, known as "abortive apoptosis," may be the reason for their presence in semen [21,23]. Activation of caspases, disruption of the mitochondrial membrane potential (MMP), and increased DNA fragmentation are some of the apoptotic features that have been identified in ejaculated spermatozoa [20,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…could be demonstrated in human sperm by immunoblot studies Taylor et al, 2004;Wang et al, 2003;Wuendrich et al, 2006). However, due to the small cytoplasmic compartment the detection of caspases in human sperm might be quite difficult.…”
Section: Colorimetric Assaysmentioning
confidence: 99%
“…Furthermore, apoptosis and capacitation have an inverse relation, which suggests that sperm undergoing capacitation are non-apoptotic, consequently apoptotic sperm have a lower ability to undergo capacitation [30]. Therefore, not all the external apoptotic factors, like H 2 O 2 , can induce PE externalization while they activate the capases which suggests that PS externalization in sperm post-ejaculation is not directly associated with apoptosis [34]. With these in mind, it can be concluded that EPS in ejaculate before capacitation may be an indicator of abortive apoptosis, however, increase in EPS following exposure of sperm to capacitation medium and induction of an acrosome reaction are part of the physiological process to achieve fertilization [32].…”
Section: Discussionmentioning
confidence: 99%